Storage and viability of Cabralea canjerana (Vell.) Mart. seeds - Grunennvaldt, Renata Lúcia; Cantarelli, Edison Bisognin; Salamoni, Adriana Tourinho (Comunicata Scientiae, 2014)
This study aimed to establish protocols for storage, germination and viability seed C. canjerana. Forthe promotion of fruit dehiscence, they were placed in the tray at room temperature (20°C) andin plastic bags at 25°C. In storage, the seeds were stored in paper envelopes and sealed becker.To test the tetrazolium’s test, seeds were submerged by 1, 2 or 3 hours in the tetrazolium salt to 1%.Germination tests in the laboratory and in the greenhouse were conducted at different times of seedstorage. The results showed that two hours of immersion of the seeds in the tetrazolium salt to 1% areeffective for determining viability. Furthermore, one can understand the effectiveness of storage offruits in plastic bags at 25°C for up to seven days to promote dehiscence and seed storage in paperenvelopes at 25°C for up to 10 days. The germination in petri dishes is effective when the seeds arestored in paper bags for up to one week, at 25ºC. In the greenhouse, the germination test can beused when the seeds are stored for up to 20 days in plastic bags at 5°C.